Answer:
w=6
Step-by-step explanation:
P=2(L)+2(w)
48= 2(18)+2w
48=36+2w
12=2w
w=6
checking;
48= 2(18)+2(6)
48= 36+12
48= 48
Answer:
93
Step-by-step explanation:
by remainder theorem p(3) is the remainder
and therefore it is 93
1. 18
2.8
3.-1
<h3>What is expression?</h3>
An expression is a set of terms combined using the operations +, – , x or ,/.
Given:
1. 22 − 1 (4)
=22- 1*4
= 22-4
= 18
2. 2 + 2 (3)
=2+2*3
=2+6
=8
3. 1 − 2
= -1
Learn more about expression here:
brainly.com/question/14083225
#SPJ1
Answer:
66.390
Step-by-step explanation:
Seven and Seventy-Five Hundredths